2012
DOI: 10.1128/aem.01119-12
|View full text |Cite
|
Sign up to set email alerts
|

Proximity-Dependent Inhibition of Growth of Mannheimia haemolytica by Pasteurella multocida

Abstract: ABSTRACTMannheimia haemolytica,Pasteurella multocida, andBibersteinia trehalosihave been identified in the lungs of pneumonic bighorn sheep (BHS;Ovis canadensis). Of these pathogens, Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

3
15
0

Year Published

2013
2013
2020
2020

Publication Types

Select...
8
1

Relationship

1
8

Authors

Journals

citations
Cited by 22 publications
(18 citation statements)
references
References 30 publications
3
15
0
Order By: Relevance
“…These results are consistent with our previous in vitro demonstration that B. trehalosi and P. multocida inhibit the growth of M. haemolytica (Dassanayake et al 2010a;Bavananthasivam et al 2012). Our finding that 77% of the lung tissue samples that were culture-negative for M. haemolytica were positive by our PCR assay supports our hypothesis that culture-based methods do not accurately detect M. haemolytica in lung tissues from pneumonic bighorns.…”
Section: Discussionsupporting
confidence: 92%
See 1 more Smart Citation
“…These results are consistent with our previous in vitro demonstration that B. trehalosi and P. multocida inhibit the growth of M. haemolytica (Dassanayake et al 2010a;Bavananthasivam et al 2012). Our finding that 77% of the lung tissue samples that were culture-negative for M. haemolytica were positive by our PCR assay supports our hypothesis that culture-based methods do not accurately detect M. haemolytica in lung tissues from pneumonic bighorns.…”
Section: Discussionsupporting
confidence: 92%
“…We reasoned that detection of M. haemolytica by culture-based methods was hindered by the inhibition of its growth by B. trehalosi and P. multocida. This notion was supported by our recent finding that B. trehalosi and P. multocida inhibit the growth of M. haemolytica when cocultured in vitro in broth cultures (Dassanayake et al 2010a;Bavananthasivam et al 2012). We hypothesized that an assay more sensitive than the culture-based methods would detect M. haemolytica in pneumonic lung tissues more accurately.…”
Section: Introductionmentioning
confidence: 85%
“…jejuni affects the microbiota or that constituents of the microbiota affect C. jejuni independent of the host, as has been observed for other pathogenic bacteria [80,81,82,83]. In conclusion, we observed that high density colonization of the cecum by C.…”
Section: Discussionsupporting
confidence: 83%
“…) and Pasteurella multocida (Bavananthasivam et al . ) have previously been described to inhibit M. haemolytica by proximity‐dependent mechanisms. Thus, bacterial competition has an important role in the respiratory tract and perhaps commensals could be used as probiotics to inhibit pathogenic bacteria.…”
Section: Introductionmentioning
confidence: 99%